A massive pericardial effusion in South Africa is not always due to tuberculosis - Ntshalintshali, Sipho; Mhlana, Nontembiso; Moosajee, Farzana; Abousriwiel, Riyad; George, Kiran; Du Toit, Riette (SA Heart Journal, 2020)
South Africa (SA) has a high incidence of tuberculosis. Medical conditions mimicking tuberculosis often result in erroneous treatment with antitubercular therapy (ATT) before a definitive diagnosis is made. We report on 2 cases presenting with massive pericardial effusions secondary to Still’s disease (sJIA) and Adult onset Still’s disease (AOSD). Both cases were treated with ATT, with an alternative diagnosis only considered upon poor response to therapy and the development of ATT associated side effects. Our objective is to remind clinicians of other potential differential diagnoses in the clinical scenario of massive effusive pericarditis in a tuberculosis endemic region.